STRATEGIC COMMUNICATION BY SOCH FACT CHECK AGAINST ELECTORAL DISINFORMATION IN PAKISTAN 2024 - Muhammad Zamir Awan; Weni A. Arindawati; Khairul Arief Rahman (Bajang Institute, 2025)
This study analyzes the communication strategy of SochFactCheck, a Pakistani fact-checking organization, during the 2024 General Elections. It employs Strategic Communication Theory and Qualitative Content Analysis (QCA) to examine 52 disinformation cases, focusing on how SochFactCheck structured, disseminated, and evaluated counter-narratives. Disinformation tactics included deepfakes, AI-generated political resignations, and gendered attacks primarily targeting PTI (Pakistan Tehreek-e-Insaf) leaders. Through a four-phase strategic model situational analysis, message development, message delivery, and evaluation SochFactCheck deployed a hybrid communication system integrating online platforms and offline journalist workshops. The results demonstrate SochFactCheck’s evolution from a reactive fact-checking outlet to a strategic actor capable of shaping public resilience and digital literacy. This study underscores the role of independent media in countering AI-driven political manipulation in fragile democracies